Estrutura e conteúdo de energia da comunidade de invertebrados aquáticos em reservatórios neotropicais no Estado do Paraná, Brasil. - Bagatini, Yara Moretto (2008)
Environmental factors controlling the richness, biomass, diversity and energy content of aquatic invertebrates were examined seasonally and spatially in thirty neotropical reservoirs. The seasonality was an important driving to the attributes and energy content of this community. Higher values of richness, biomass and diversity of taxa were recorded in the dry season, due to increased stability of the environment, which increases the availability of habitat and processing of allochthonous and autochthonous material. Moreover, higher energy content of invertebrates was recorded during the rainy season and for phytophilous invertebrates. The input of allochthonous material during this period, combined with the higher complexity of the food web in aquatic vegetation in general, provide greater availability of food resources for these invertebrates, especially for detritivorous and omnivorous. Differences in values of energy, between the feeding guilds, were attributed to the great flexibility of food invertebrates in neotropical regions, which is related to the availability of food resources and also to the selectivity. When analyzed the spatial variation, higher values of richness, diversity and evenness were found at the margins, while the biomass was greater in the center of the reservoirs. The heterogeneity of the substrate, less depth and greater concentration of dissolved oxygen were determining factors for the higher values of these attributes on the margins. The mesotrophic reservoirs are highlighted by the greater richness, biomass, diversity and caloric density of invertebrates. The enrichment of these environments by the intake of nutrients during the rain, and consequent increase in primary production influence the structure and functioning of the community of aquatic invertebrates in neotropical reservoirs. Thus, both the seasonal and spatial factors were important to the variation in richness, biomass, diversity, evenness and caloric content of aquatic invertebrates in neotropical reservoirs from the Paraná State.